Polish Source of Trilingual Book of Psalms from Simon Azarjin’s Book Collection - Целунова, Елена Александровна Александровна (Slavistica Vilnensis, 2018)
[full article, abstract in Russian; abstract in Lithuanian and English] The article is devoted to the textological research of the Polish text of the Book of Psalms manuscript from Simon Azarjin’s book collection written in three languages in the 17th century. The Book of Psalms represents a trilogy written inter-linearly in three languages: Church Slavonic, Greek and Polish. The Polish text as part of the Orthodox Book of Psalms makes this memorable text unique. The former author’s textological analysis was implemented and based on the Book of Psalms original source, and namely on the Polish Catholic Leopolita Bible. The present research enables us not only to clarify the specific edition of the Leopolita Bible but also to reveal one additional source of the trilogy – the Jakub Wujek Bible of 1599.